New Higher Education Model? Degree Apprenticeships as a Strategy to Modernize Apprenticeships: Rationale, Current Development in the U.S., and a Conceptual Framework - Voeller, Jooyoung (International Journal for Research in Vocational Education and Training, 2023)
Purpose: To better prepare young people for the increasingly complex world of work in the global knowledge economy, apprenticeships are receiving renewed attention in countries without a strong history of vocational education. One of the strategies to promote and modernize apprenticeships in these countries is to offer apprenticeships integrated into degree programs, known as degree apprenticeships at the tertiary level. However, little research has been done to explore this new degree pathway. The purpose of this study is to explore the rationales and recent development of degree apprenticeships in the U.S. and to present a conceptual framework for designing and delivering such programs. Approach: Through an extensive literature review, this study examines the underlying justifications for the integration of apprenticeships into degree programs. Subsequently, it delves into the current progress of degree apprenticeships in the U.S., substantiating the rationales. Finally, it explores multiple facets of degree apprenticeships, offering a conceptual framework for higher education institutions to consider when implementing such programs. Findings: This study discusses two rationales for degree apprenticeships. First, they enable permeability of vocational education credentials, one of the features of a robust apprenticeship system. Second, they also equip higher education institutions to effectively prepare young people for work in response to globalization. For these reasons, recently, community colleges, the primary vocational education providers in the U.S., have actively been implementing apprenticeships within degree programs. This study also outlines four interconnected dimensions of apprenticeships - occupational, pedagogical, relational, and aligned – as a conceptual framework for implementing degree apprenticeships. Conclusion: By providing a useful context and framework for degree apprenticeships, this study contributes to the growing body of research on apprenticeships and provides a foundation for on-going research to advance the theory and practice concerning degree apprenticeships. Future studies can explore the process of implementing degree apprenticeships using the suggested framework and develop strategies to further modernize apprenticeships based upon this study.